2005
DOI: 10.1353/hsj.2005.0019
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Physical Education Teachers' Beliefs and Practices in Teaching Students with Severe Disabilities: A Descriptive Analysis

Abstract: The purpose was to describe the beliefs and practices of general physical education (GPE) teachers at the high school level on inclusion and teaching students with severe disabilities. Participants were two experienced GPE teachers at separate suburban high schools. The research paradigm was descriptive using a combination of naturalistic observation and interviewing (Fontana & Frey, 2000; Gay, 1996). Data were collected from eighteen lessons using field notes, wireless microphones, a video camera, an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 20 publications
1
35
0
8
Order By: Relevance
“…Una inadecuada preparación de los profesores conlleva un efecto negativo en la percepción de competencia, confianza y actitudes para con el proceso inclusivo (Ammah, y Hodge, 2005;Hutzler, Zach, y Gafni, 2005;Ocete-Calvo, 2016), por lo que la formación orientada para la mejora del sentimiento de autoeficacia se convierte en un aspecto fundamental. La teoría de la autoeficacia de Bandura (Bandura, 1989) es un elemento relevante de la Teoría Social-Cognitiva, sirviendo de marco de referencia para poder evaluar la autoconfianza percibida, en este caso de los profesores de EF para con la inclusión de alumnos con discapacidad en sus clases.…”
unclassified
See 1 more Smart Citation
“…Una inadecuada preparación de los profesores conlleva un efecto negativo en la percepción de competencia, confianza y actitudes para con el proceso inclusivo (Ammah, y Hodge, 2005;Hutzler, Zach, y Gafni, 2005;Ocete-Calvo, 2016), por lo que la formación orientada para la mejora del sentimiento de autoeficacia se convierte en un aspecto fundamental. La teoría de la autoeficacia de Bandura (Bandura, 1989) es un elemento relevante de la Teoría Social-Cognitiva, sirviendo de marco de referencia para poder evaluar la autoconfianza percibida, en este caso de los profesores de EF para con la inclusión de alumnos con discapacidad en sus clases.…”
unclassified
“…Son pocos los trabajos en la literatura que han aplicado la teoría de la Autoeficacia en EFI (Ammah, y Hodge, 2005;Hutzler et al, 2005;Ocete-Calvo, 2016), la cual puede utilizarse para evaluar las creencias mostradas por los profesores durante su práctica profesional y predecir sus estrategias en la práctica (Kozub, y Lienert, 2003), siendo además un constructo válido para evaluar las creencias de auto-competencia del profesorado como un factor predictor de su actitud hacia la inclusión de alumnos con discapacidad (Taliaferro, Hammond, y Wyant, 2015).…”
unclassified
“…However, findings indicated that GPE teachers have not been adequately trained to work with students who have disabilities (Ammah & Hodge, 2006;Block & Obrusnikova, 2007;Hardin, 2005;Hutzler, 2003;LaMaster, Gall, Kinchin, & Siedentop, 1998). It is questionable as to whether PETE programs in higher education provide adequate training to PETE students in regards to dealing with students who have disabilities and are in their GPE classes.…”
Section: Literature Review In Infusion Approach Curriculummentioning
confidence: 99%
“…Since a lack of academic preparation in Physical Education Teacher Education (PETE) program was one of the primary reasons for lack of competence in GPE teachers toward including students with disabilities (Ammah & Hodge, 2006), it is necessary to develop and implement an Adapted Physical Education (APE) educational supplement throughout PETE curriculum. The purpose of this study was to explore whether an APE e-learning supplement would have an impact on the level of self-efficacy and content knowledge of pre-service teachers related to including students with intellectual disabilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation